J.K. Lasser's from eBay to Mary Kay : - Carter, Gary W. (John Wiley & Son, 2006)
Today, millions of people are making either a full- or part-time living selling things on Internet auction sites like eBay. Still more are making a living selling products from their homes--think Mary Kay and Avon. If you're just entering the home-based or online business arena, you might not be aware of your potential tax liability. With J.K. Lasser's From eBay to Mary Kay, leading tax consultant Gary Carter walks you through the challenges of accounting for a home-based business. Topics covered throughout this comprehensive guide include: Can you deduct the use of your home?; Are there ways to avoid taxes entirely?; What types of taxes might you owe?; How do you account for your inventory?; What are the rules on collecting sales and use taxes?